Linking English and Cyber Security: Innovative Methods to Enhance Comprehension and Implementation of Security Measures - Swapna, P. Kalyani (Language, Literature and Education: Research Updates Vol. 2, 2025)
Language proficiency and cyber security are intimately related in today's digital world. Effective communication becomes crucial for comprehending, putting into practice, and upholding security protocols as cyber threats change. This chapter examines how cyber security awareness, training, and the actual implementation of security measures are improved by fluency in the English language. People are better able to comprehend security requirements, evaluate cyber dangers, and communicate more effectively in defence plans when English language teaching is combined with cyber security expertise. In order to promote a more secure digital environment, the chapter highlights the value of language competency as a tool for enhancing cybersecurity procedures and offers a framework for integrating language instruction with security education.